(untitled) (International Journal of Medical and Surgical Sciences, 2016)
The upper limb arterial variations are justified by the embryological origin of all the limb. The birth of the radial artery above the joint line of the elbow is one of the most frequent anomalies and its importance is increasing in percutaneous procedures on the radial artery, in coronary catheterizations and the increasingly used of the ra- dial flap in reconstructive surgery. Its superficial way favors injuries and the possibility of confusion with veins that can cause accidental drug performing injections in these arteries with serious consequences. Knowledge of arterial variations of the upper limb, especially the radial artery presented in this research, is essential when planning clinical and surgical approaches that involves them.